What are the sources, negative impacts and mitigation measures regarding microplastic pollution? A case study of the Durban harbour - Ngcobo, Princess Mbalenhle (My University, 2023)
This study aims to present mitigation measures to the problem of microplastic pollution in the Durban Harbour. Before proposing measures to mitigate microplastic pollution in the Durban Harbour, the report will first assess the sources of microplastics and their environmental effects on the study site. The growing population has been accompanied by an increase in plastic waste in the environment. Poor waste management systems, especially in developing countries, have resulted in microplastic pollution in water systems. As a result, high levels of microplastics have been reported in South African water bodies. The high concentration of microplastics in the environment can pose adverse effects on biota, including humans. This study followed a qualitative research approach and made use of a single case study research strategy as part of the research methods. Five interviews were conducted with microplastic experts, including those researching microplastics in the Durban Harbour. The interviewees were selected through purposive sampling. The study findings suggest that the Durban Harbour received microplastics from different sources, including the three rivers (such as uMbilo, uMhlatuzana and aManzimyama rivers) and harbour activities (such as fishing, cargo spillage and recreational activities). As a result, everyone has a role to play in addressing the issue of microplastics in the Durban Harbour. This study affirms the need for collaboration between experts from different disciplines, the government, industries and communities. Urban Managers can employ the GET matrix (which stands for Governance, Education and Technology) to effectively address pollution in the harbour.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Urban Studies to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2023